(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
Nowadays securities market has a special importance to national economy as a key sector of a state’s financial system condition, and it also serves asareference point for foreign investors. The Kazakhstan securi-ties market is characterized by underdevelopment ofits stock market. Key problem are low liquidity of domestic stock market, the need for creation of new financial instruments, trade activization, and also the attraction of investments into real sector of econom and etc. This article identifies main problems of securities marketand provides analysis of main reasons for which securities market does not develop properly. The author having analyzed a key indicator – a capitalization to GDP ratio, concludes that the securities market is notwell-developed. Moreover, main measures for increasing securities market attractiveness and prospect of its development are considered.